Female-headed single-parent households and poverty in Costa Rica - T.H. Gindling; Luis Oviedo (CEPAL Review, 2008)
Average real family incomes rose in Costa Rica in the late 1990s and at the start of the new decade, but poverty rates did not fall. Here it is argued that economic growth in the country did not translate into reduced poverty during this period because of changes that took place in household structure and in the labour market, and that these changes had an important gender dimension Specifically, a rising proportion of female-headed single-parent households led to an increase in the number of women with children entering the labour force, many of them for the first time. Many of these mothers were unable to find or unwilling to accept full-time work in the higher-paying formal sector and ended up unemployed or working part-time as self-employed workers. These labour market phenomena contributed to low incomes for vulnerable households, especially single-parent households headed by women.